2014
DOI: 10.1177/1744259114526350
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modelling analysis of a three-layer wall with phase-change thermal storage in a Chinese solar greenhouse

Abstract: To improve the construction methods of Chinese solar greenhouse wall to enhance the heat storage, we proposed a three-layer wall with phase-change materials, namely, an inner wall layer built with the phase-change materials, an outer insulating layer and a load-bearing wall layer built with heavyweight materials between the two. Based on the field experiment and the proposed valuation indexes of the three-layer wall, the dynamic heat storage characteristics of the wall have been analysed and discussed. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…This type of PCM was developed for building applications, a shape-stabilized solid-liquid PCM composed of paraffin encapsulated by high density polyethylene (HDPE). This type of PCM has been successfully integrated into building fabrics and showed good performance on both promoting the thermal storage of the fabric and increasing its thermal insulation [25,32,33]. Table 3 lists some main thermal properties of the BJUT PCM and Table 4 provides its enthalpy at various temperature conditions, as reported by Chen et al [34], with major phase changing temperatures ranging between 23.1˝C and 24.0˝C.…”
Section: Experimental Phase Change Materialsmentioning
confidence: 99%
“…This type of PCM was developed for building applications, a shape-stabilized solid-liquid PCM composed of paraffin encapsulated by high density polyethylene (HDPE). This type of PCM has been successfully integrated into building fabrics and showed good performance on both promoting the thermal storage of the fabric and increasing its thermal insulation [25,32,33]. Table 3 lists some main thermal properties of the BJUT PCM and Table 4 provides its enthalpy at various temperature conditions, as reported by Chen et al [34], with major phase changing temperatures ranging between 23.1˝C and 24.0˝C.…”
Section: Experimental Phase Change Materialsmentioning
confidence: 99%
“…Fig. 1 A typical clustered facility established on the Gobi land in northwestern China; the system consists of (a) several (up to hundreds) of individual cultivation units, and (b) microclimatic conditions in each cultivation unit are monitored through a centralized controlling center A critical component of each cultivation unit is the north wall that is built from locally available materials such as clay bricks (Wang et al 2014), crop straw blocks (Zhang et al 2017), common bricks with styrofoam (Xu et al 2013), fly ash masonry units (Xu et al 2013), clay blocks mixed with cement mortar (Chen et al 2012), rammed earth (Guan et al 2013), or raw soil incorporated with concrete blocks. In some units, the north wall is constructed from "phase-changing material" to optimize heat storage and exchange, and, therefore, reduce temperature fluctuations for plant growth (Guan et al 2012).…”
Section: A Brief Review Of Infrastructure Of Gobi Land Systemsmentioning
confidence: 99%
“…Prediction results indicated that PCM could decrease the swing of indoor air temperature during the 24h period by 3-5°C. Guan et al [22] developed a three-layer wall with PCM for solar greenhouses. By doing this, the effective heat storage capacity of the wall was increased by 12.2%-14.0%, and the indoor air temperature at night was raised by 2.5°C.…”
Section: Introductionmentioning
confidence: 99%
“…For the experimental wall, the thickness of the thermal-stable layer inside the wall has reached 750mm. Guan et al [22] also suggested that for a three-layer PCM wall with a thickness of 900mm, the part that was affected by solar gains was only about 300mm, and the thermal-stable layer had a thickness of 400mm. Wang et al [29] carried out a numerical study to predict the temperature distribution inside the north wall with an average thickness of 3.0m.…”
Section: Introductionmentioning
confidence: 99%